A Proactively Maintained Quality of Service Infrastructure for Wireless Mobile Ad Hoc Networks - Khaled Alzoubi, Moussa Ayyash, Donald Ucci and (International Journal of Communication Networks and Information Security (IJCNIS), 2010)
.